The Influence of Zakat Empowerment and Business Assistance on Mustahik Welfare through Business Growth in Aceh - Eka Nurlina; Nurma Sari; Hendar Halim; Khairul Umuri (Jurnal Investasi Islam, 2026)
This study aims to analyze the effect of zakat empowerment and business assistance on the welfare of mustahik (recipients of the productive zakat program), with business growth as a mediating variable. The study used a quantitative approach with primary data obtained from 155 mustahik (recipients of the productive zakat program) in Banda Aceh City and Aceh Besar Regency. The analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results show that zakat empowerment and business assistance have a positive and significant effect on business growth. Furthermore, zakat empowerment and business assistance also have a positive, significant effect on the welfare of mustahik. Business growth was shown to significantly influence mustahik welfare and mediate the relationship between zakat empowerment and mustahik welfare. However, business growth did not mediate the relationship between business assistance and mustahik welfare. These findings indicate that the effectiveness of productive zakat in improving mustahik welfare depends on the program's ability to encourage sustainable business growth and to integrate capital provision and structured mentoring.